Use of multi-criteria decision making method for calculating of secondary school efficiency: the case of vocational secondary schools in the Pardubice Region - Chlebounová, Denisa; Provazníková, Romana (Vysoká škola báňská-Technická univerzita Ostrava, 2019)
Multi-criteria decision making techniques are extensively used in selecting the best alternative among the available options, assessed according to selected criteria. It is a suitable tool for evaluating and comparing schools because school efficiency measurement can be seen as a decision-making problem. The aim of this paper is to evaluate vocational secondary schools established by the Pardubice Region using appropriate selected criteria describing efficiency and then rank the schools according to these criteria. We chose suitable criteria which are mainly based on pupils' demand and demand for skilled workers in the labour market. We used the Weighted Sum Method for our analysis. The resulting order of schools ranked according to their efficiency shows that supported fields should be medical, technical and on the other hand, fields that currently show low efficiency are agricultural or gastronomic fields. Our results might be an inspiration for designing an optimal network of vocational secondary schools in the Pardubice Region.
Využití vícekriteriální analýzy variant pro výpočet efektivnosti středních škol: případ středních odborných škol v Pardubickém kraji
Keywords: Efficiency; secondary schools; decision making; multi-criteria; weighted sum method; efektivnost; střední školství; rozhodování; vícekriteriální analýza variant; metoda váženého součtu